2021
DOI: 10.32942/osf.io/qxf4z
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A 25-years population dynamics of sika deer in Kyushu Island, Japan: Estimation using vector autoregressive spatiotemporal model and evaluation of a large-scale management

Abstract: Regional management of large herbivore populations is known to be effective in reducing local economic damages and conserving local endemic plants. However, herbivores often move across management areas, and the effect of population management on a large spatial scale is poorly understood, even though it is necessary to use a large-scale approach across multiple management units to implement appropriate management. In this study, to better understand large-scale management and improve management efficiency, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 62 publications
1
7
0
Order By: Relevance
“…High regional culling pressure decreased browsing damage in that region. In contrast, Suzuki et al (2021a) reported there was little effect of culling on deer abundance at the prefectural scale. These findings highlight the importance of spatial scale in the management of large herbivores.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…High regional culling pressure decreased browsing damage in that region. In contrast, Suzuki et al (2021a) reported there was little effect of culling on deer abundance at the prefectural scale. These findings highlight the importance of spatial scale in the management of large herbivores.…”
Section: Discussionmentioning
confidence: 95%
“…Hunters report the locations of culled deer to the Kumamoto prefectural government, which tallies these data by grid meshes (5 km latitude × 5 km longitude). The annual number of culled deer has increased, with a 4‐fold increase between 1999 (4,335 deer) and 2017 (17,360 deer; Suzuki et al 2021 a ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations